STUDI PENGEMBANGAN PROTOTYPE PEMANFAATAN DIGITAL TECHNOLOGY DALAM PEMBELAJARAN MENULIS BAHASA INDONESIA DI SD - Silky Goswara; Jap Tji Beng; Sri Tiatri (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Digital technology is an integral part of people's lives. One of the functions of digital technology is used for teaching and learning. The benefits of the research of this thesis is to examine and test the development of Technology Acceptance Model factors that generate revenue and impact of use digital technology to learn writing Indonesia language. The method in this research is quantitative research methods and qualitative research methods.The purpose of this research is to look how the influence of percieved ease of use variable and  percieved usefulness variabel to behavior intention variable in using the prototype writing Indonesian language for the elementary student. The result of this research is the ease of use of the prototype affects the benefits and make student want to use that prototype  writing Indonesian language. Key wordsDigital Technology, Technology Acceptance Model, Percieved Ease of Use, Perceived Usefulness, Behavior Intention.